1996
DOI: 10.1111/j.2042-7158.1996.tb03940.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Hydroxytryptamine Agonists on Myoelectric Activity of the Forestomach and Antroduodenal Area in Sheep

Abstract: To increase knowledge of the role of 5-hydroxytryptamine (5-HT) receptors in the regulation of reticuloruminal, omasal and antroduodenal myoelectric activity in sheep, the effects of 5-HT agonists on forestomach and antroduodenal myoelectric activity have been investigated in conscious sheep. 5-Carboxamidotryptamine, methysergide, alpha-methyl-5-HT, 2-methyl-5-HT, cisapride, zacopride or metoclopramide were infused intravenously for 5 min and myoelectric recordings were obtained from electrodes chronically imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…, 2000). In an electromyographical study on conscious sheep (Plaza et al. , 1996), α ‐M‐5‐HT evoked a dose dependent increase in antral activity and a dose‐dependent inhibition of the myoelectrical activity of both the reticulorumen and the omasum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2000). In an electromyographical study on conscious sheep (Plaza et al. , 1996), α ‐M‐5‐HT evoked a dose dependent increase in antral activity and a dose‐dependent inhibition of the myoelectrical activity of both the reticulorumen and the omasum.…”
Section: Discussionmentioning
confidence: 99%
“…, 1994). The effects of 5‐HT agonists on myoelectric activity of the forestomach and antroduodenal area were investigated (Plaza et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In another study in sheep, 5-HTR 1A , 5-HTR 2 , 5-HTR 3 , and 5-HTR 4 are reported to be involved in the regulation of forestomach motility occasionally recorded concomitantly to duodenal phase III activity (21,32). Furthermore, 5-HT is also implicated in the regulation of MMC patterns in the abomasum and proximal small intestine (17,(19)(20)(21)27,33), but little is known about the role of the respective 5-HTR subtypes involved in motility control in ruminants.…”
Section: Introductionmentioning
confidence: 92%
“…However, the serotoninergic pathways were predominantly studied in humans and rodents. The 5-HT was shown to be involved in the initiation and regulation of the myoelectric migrating complex (MMC), in the peristaltic reflex, in the regulation of stomach, small intestine and colon motility, as well as in intestinal secretion (4,9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The mechanisms of action of 5-HT in the digestive tract are not completely understood and the role of 5-HTR subtypes in the regulation of GI motility differs among species and locations along the GI tract (9,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the result of Jones et al (1994) that recorded short half-life of metoclopramide and suggested use continuous release device to produce prolonged effect. Metoclopramide is an antagonist at dopaminergic (D2) receptors and a serotonin (5-hydroxytryptamine; 5-HT) agonist at 5-HT4 receptors and antagonist at 5-HT3 receptors (Plaza et al 1996). In humans, it is also a neuroleptic agent that induces extrapyramidal activity with apparent adverse effect, which is more likely to occur in children (Hyams et al 1986;Cézard et al 2003).…”
Section: Discussionmentioning
confidence: 97%